Evaluation of the Quality of Some Water Stations on the Tigris River Using the Iraqi Water Quality Index (Iraq WQI) - Al-Saedy, Rawaa Nader; Al-Hassany, Jinan S.; Al-Ramahi, Fouad K.Mashee (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Water quality assessment is important for water resource management. The current study focuses on the analysis of monitoring water quality data of the Tigris River in Iraq by applying the Iraqi Water Quality Index (WQI). Twenty-one parameters Quality standards were taken along the river for three governorates and for eight stations, starting from Salah al-Din, north of Baghdad, with one station (Samarra), and Baghdad represented by three stations (Al-Mutha Bridge, Atifia, Jadriya) and south of Baghdad represented by Kut Governorate (Aziziyah, Zubaydah, Numaniyah, Al-Muftah), and included Quality standards nine standards were used for the purposes of living organisms, including (pH, T.w., PO4, NO3, Cl, NO2, TDS, Tur, DO) and eight standards for the purpose of fresh water maintenance (NO3, Cl, TDS, Tur., DO, BOD5, pH, PO4). The result showed that the application the Iraqi WQI decrease in the quality of the river water and its suitability for the neighborhoods living towards the north of Baghdad (Samarra), it reached (71.38 poor) in the dry season. While the highest value was (175.21, unsuitable) in southern Baghdad (Numaniyah) during the dry season, the water quality index for the purpose of maintaining fresh water recorded a decrease in station2 (Al-Muthanna Bridge) for the wet season, while the index value increased in station7 (Numaniyah). for the dry season. The results of the two seasons (wet and dry) coincided for the purposes of living creatures, while the index differed for the two seasons for the purposes of fresh water conservation; this is due to the increase pollution in the river as a result of human activities. Therefore, the guide used in this study could be applied to all rivers in Iraq based on the reliability of the quality index. The water in Iraq no longer requires the use of indicators designed for water in other countries